The Grammatical Verbs Categories in the English and Uzbek Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the grammatical verb categories in English and Uzbek, focusing on the ways in which tense, aspect, mood, and voice are encoded and function in these typologically distinct languages. Verbs serve as the core of predicate structure, conveying not only actions and states but also temporal, modal, and evaluative nuances. English, as an analytic language, expresses grammatical categories primarily through auxiliary verbs, inflection, and syntactic structures, whereas Uzbek, as an agglutinative language, relies on suffixes, mood markers, and evidential forms to encode similar meanings. The study employs a contrastive approach to highlight both universal cognitive strategies in verb categorization and language-specific mechanisms shaped by typology and culture. Findings reveal that while both languages share the functional goal of representing events and speaker perspective, they differ in morphological encoding, syntactic realization, and semantic nuance, providing insights for comparative grammar, language teaching, and cross-linguistic understanding.